Preliminary Analysis: Is there enough definitional clarity of food literacy for food security? - Sneha Roy; Jeffrey Zacharakis (Adult Education Research Conference, 2022)
We conducted a systematic review of the literature (2001 - 2021) to investigate the definitional clarity of food literacy for food security among adults. Our findings suggest the need for a more precise definition of food literacy.
Keywords: Food literacy; foods security; adults; sustainable development goals